Analisis Hasil Belajar Praktikum Ipa Ditinjau Dari Kemampuan Afektif Siswa Pada Kelas Viii DI Mts N Surakarta Ii Tahun Ajaran 2014/2015 - , Yuswanto; Anif, M.Si, Dr. Sofyan Anif, M.Si (2016)
The result of the learning is the ability that is owned by students after they experience their study or activity during the teaching and learning process, whether about the concept or theory that is given to the students. The result of the learning, students will understand the ability of mastering the theory or practice that is taught to the students, so that, the ability that exists in their aspects of life will appear on their changing of the behavior quantitatively. The references about data of learning result which are got, may be a motivation for students to learn more diligently on the next teaching and learning process. This research aims at knowing the influence of student's affective ability through learning result of the practice of Natural Science in MTs Negeri Surakarta II 2015/2016 academic year. This research is a quantitative-explanative which uses a test (t). The population of the research is students class VIII in MTs Negeri Surakarta II 2015/2016 academic year. Sample of this research is class VIII A1 and VIII A2 in MTs Negeri Surakarta II. Technique of collecting data of the research is through observation and documentation. The result of the study is value sig. 0,000 < 0,05 so the result of Natural Science practice is influenced by the student's affective ability in MTs Negeri Surakarta II 2015/2016 academic year. In this case, the conclusion is that the student's learning result in practicing Natural Science is influenced by student's affective ability in MTs N Surakarta II 2015/2016 academic year.